Visualizing radiofrequency lesions using delayed‐enhancement magnetic resonance imaging in patients with atrial fibrillation: A modification of the method used by the University of Utah group. Issue 2 (7th August 2014) - Kiuchi, Kunihiko; Okajima, Katsunori; Shimane, Akira; Yokoi, Kiminobu; Teranishi, Jin; Aoki, Kousuke; Chimura, Misato; Tsubata, Hideo; Miyata, Taishi; Matsuoka, Yuuki; Toba, Takayoshi; Ohishi, Shogo; et al.
Abstract: Background: Atrial tissue fibrosis has previously been identified using delayed‐enhancement MRI (DE‐MRI) in patients with atrial fibrillation (AF). Although the clinical importance of DE‐MRI is well recognized, the visualization of atrial fibrosis and radiofrequency (RF) lesions has still not been achieved in Japan, primarily because of the differences in contrast agents, volume‐rendering tools, and technical experience. The objective of this study was to visualize RF lesions by using commercially available tools. Methods: DE‐MRI was performed in 15 patients who had undergone AF ablation (age, 59±4 years, left atrium diameter, 40±2 mm). Specific parameters for MR scanning obtained from previous reports were modified. Results: Of the 15 images, the images of three patients were uninterpretable owing to low image quality. RF lesions could be visualized in 8 (67%) of the 12 patients. Conclusions: In the current study, we successfully demonstrated that RF lesions could be visualized in Japanese patients using DE‐MRI, although only commercially available tools were used.